2018
DOI: 10.1001/jamaophthalmol.2018.2166
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pediatric Atopic Dermatitis and Cataract Development and Surgery

Abstract: IMPORTANCE There is a paucity of data addressing the risk of cataract development in pediatric patients with atopic dermatitis (AD). OBJECTIVE To investigate the association of AD with subsequent cataract development and cataract surgery in a Korean pediatric population. DESIGN, SETTING, AND PARTICIPANTS This population-based retrospective longitudinal cohort study used nationally representative data from the Korean National Health Insurance Service database from 2002 to 2013. Incident AD cases, consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Atopic dermatitis (AD) is a common chronic inflammatory skin disease of childhood, affecting between 10% and 20% of children in industrialised countries [ 1 3 ]. Patients with AD are frequently predisposed to ocular complications, such as blepharitis, keratoconjunctivitis, keratoconus, cataract, and rhegmatogenous retinal detachment (RRD) [ 1 , 4 , 5 ]. Of these, RRD is the most serious complication; it can lead to the loss of vision [ 6 ], which could be a great obstacle in life for young patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atopic dermatitis (AD) is a common chronic inflammatory skin disease of childhood, affecting between 10% and 20% of children in industrialised countries [ 1 3 ]. Patients with AD are frequently predisposed to ocular complications, such as blepharitis, keratoconjunctivitis, keratoconus, cataract, and rhegmatogenous retinal detachment (RRD) [ 1 , 4 , 5 ]. Of these, RRD is the most serious complication; it can lead to the loss of vision [ 6 ], which could be a great obstacle in life for young patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 4 , 7 11 ] Postulated mechanisms of RRD in those with AD include trauma such as rubbing eyes repeatedly for relieving itching, which affects the occurrence of RRD. [ 4 , 7 11 ] In addition, one of the other ophthalmic complications of AD is cataract, and it is reported that cataract surgery itself can cause RRD [ 5 , 12 ]. Therefore, it is important to analyse the association between AD and RRD occurrence in conjunction with several comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“… 8 However, the type of cataract in these patients is usually anterior or posterior sub-capsular unlike in our patient who had anterior capsular plaques as well as nuclear lenticular opacities. 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…An association between the development of cataracts and increased IgE serum levels, the duration of the topic cortical therapy at the facial level, and systemic corticoid treatment was not demonstrated. A Danish studio established a correlation between atopic dermatitis and cataracts that especially applies to patients under 50 [ 52 , 53 ].…”
Section: Extra-cutaneous Clinical Manifestationsmentioning
confidence: 99%